PENGARUH KEPEMIMPINAN SITUASIONAL DAN POLA KOMUNIKASI TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. PLN TARAKAN MITRA PT. PLN (PERSERO) ULP WOHA - Firmansyah Kusumayadi (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This research aims to determine the positive and significant influence of situational leadership and communication patterns on employee work discipline at PT. PLN Tarakan Partners PT. PLN (Persero) ULP Woha. This type of research is associative using quantitative data. The population and sample in this research were 55 employees using a total sampling technique. Data collection techniques include observation, interviews, questionnaires, documentation. Data analysis techniques use validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, coefficient of determination, t tests and f tests with the help of SPSS version 24 for Windows. The research results show that there is a positive and significant influence of situational leadership and communication patterns on employee work discipline at PT. PLN Tarakan Partners PT. PLN (Persero) ULP Woha.